Relationship between mozzarella yield and milk composition, processing factors, and recovery of whey constituents - Sales, D. C.; Rangel, A. H. N.; Urbano, S. A.; Freitas, Alfredo R.; Tonhati, Humberto [UNESP]; Novaes, L. P.; Pereira, M. I. B.; Borba, L. H. F. (Elsevier B.V., 2017)
Our aim was to identify the relationship between mozzarella cheese yield and buffalo milk composition, processing factors, and recovery of whey constituents. A production of 30 batches of mozzarella cheese at a dairy industry in northeast Brazil (Rio Grande do Norte) was monitored between March and November 2015. Mozzarella yield and 32 other variables were observed for each batch, and divided into 3 groups: milk composition variables (12); variables involved in the cheesemaking process (14); and variables for recovery of whey constituents (6). Data were analyzed using descriptive statistics, Pearson correlation, and principal component analysis. Most of the correlations between milk composition variables and between the variables of the manufacturing processes were not significant. Significant correlations were mostly observed between variables for recovery of whey constituents. Yield only showed significant correlation with time elapsed between curd cuttings and age of the starter culture, and it showed greater association with age of the starter culture, time elapsed between curd cuttings, and during stretching, as well as with milk pH and density. Thus, processing factors and milk characteristics are closely related to dairy efficiency in mozzarella manufacturing.
Keywords: Bubalus bubalis; dairy product; efficiency; industry; cheese